The inspiration of geometrical concepts in Mengkuang weaving motifs / Rozita Shamsuddin ... [ et al.] - Shamsuddin, Rozita; Muhamad, Rahaidah; Wan Bakar, Wan Norliza; Raja Mohd Yusof, Raja Norazila (Faculty of Art and Design, 2023)
Every beautiful piece reflects a labour of love and the story of a dying art. Passed from generation to generation, these skills are now possessed by a few master crafts persons. The art of weaving dried leaves of various plants has been a part of many indigenous cultures for centuries. Mengkuang leaves are commonly used to make household items such as floor mats, rice holders, food covers, and different kinds of bags and baskets. Some new products that have been introduced in recent times include purses and lamp shades, sometimes innovatively combined with textiles to widen their use and appeal. Weaving is a form of art that involves the interlacing of sets of leaf blades processed according to certain disciplines to create mats and house walls which can be seen almost everywhere. Woven products are made from tropical plants and therefore making them widely available in the country. In the art of Mengkuang weaving design, the geometrical shape in weaving is divided into three categories like original geometrical design, natural geometrical design, and arrangement of the geometrical design. The original geometrical designs have existed for many years. The geometrical arrangement design is a combination of the natural geometrical design in producing an abstract. Motifs or Kelarai is a design found in the Mengkuang weaving motifs. Kelarai is a motif that results from a weaving pattern. Kelarai is made in a variety of motifs and its role is the same as the floral pattern in weaving. The name will be different if woven in different shapes, sizes and arrangements. The objective of this study is to analyse the geometrical element in the Mengkuang weaving motifs or Kelarai. A study on geometrical concepts focusing on 8 motifs out of 51 motifs produced by the weavers in Bukit Tanah, Kelantan to analyse mathematical concepts that appear on the Mengkuang weaving motifs.